2020
DOI: 10.1253/circj.cj-20-0264
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Response Occurring at 3 Months After Everolimus-Eluting Cobalt–Chromium Stent Implantation in Patients With ST-Segment Elevation Myocardial Infarction vs. Stable Coronary Artery Disease

Abstract: occurs within 3 months after DES implantation in AMI patients and that delayed vessel healing at the thrombotic lesion is observed within 30 days after DES implantation. 1,3-6 Thus, rapid progression of vascular healing during the early phase, together with thromboresistance, is the desired outcome of DES for AMI patients.Cobalt-chromium everolimus-eluting stent (CoCr-EES), Stent thrombosis (ST) rarely occurs in patients undergoing 2nd-generation drug-eluting stent (DES) implantation for coronary artery diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the incidence of late and very late stent thrombosis has been remarkably reduced by newer-generation DES, with > 70% of stent thrombosis events occurring in the early post-procedural phase. In addition, we previously reported that arterial healing after DP-EES and BP-sirolimus-eluting stent implantation was significantly delayed, especially in the early phase in STEMI patients than in those with stable coronary artery disease [12,13]. These findings increase the clinical importance of investigating early-phase vascular healing after stenting, particularly in the STEMI setting [1,14].…”
Section: Arterial Healing In the Early-phase (Post-pci To 2-week Foll...mentioning
confidence: 84%
“…Moreover, the incidence of late and very late stent thrombosis has been remarkably reduced by newer-generation DES, with > 70% of stent thrombosis events occurring in the early post-procedural phase. In addition, we previously reported that arterial healing after DP-EES and BP-sirolimus-eluting stent implantation was significantly delayed, especially in the early phase in STEMI patients than in those with stable coronary artery disease [12,13]. These findings increase the clinical importance of investigating early-phase vascular healing after stenting, particularly in the STEMI setting [1,14].…”
Section: Arterial Healing In the Early-phase (Post-pci To 2-week Foll...mentioning
confidence: 84%
“…The final uncovered rate was excellent, approaching zero at 12 months. We previously conducted the MECHANISM-AMI study using CoCr-EES [ 9 ]. Although not uniformly comparable, the uncovered strut rate after 3 months of BP-SES implantation was approximately 10%, higher than that of CoCr-EES at 5.5%.…”
Section: Discussionmentioning
confidence: 99%
“…OFDI analysis was performed by two independent core laboratories (ULTIMASTER AMI: Kobe Cardiovascular Core Laboratory (KCCL), Kobe University Graduate School of Medicine, Kobe, Japan, MECHANISM-ULTIMASTER Elective: ICAL, Iwate Medical University, Yahaba, Japan) using OFDI software (Terumo, Japan) and according to the standard operating procedure of the MECHANISM-ULTIMASTER study and published methods (Fig. 2) [7][8][9]. Inter-and intra-observer reproducibility were demonstrated in supplemental file.…”
Section: Ofdi Image Analysis and Study Endpointsmentioning
confidence: 99%